Effects from treating moderate- to high-risk obesity patients with anti-obesity medication from a societal perspective - Stephanie Reitzinger; Thomas Czypionka (Scientific Reports)
Abstract Obesity is a global health concern with new medication treatment options. So far, research on how programs with newer anti-obesity medication (AOM) for the moderate- to high-risk population can mitigate the prevalence of obesity and reduce the economic burden of society is limited. We aimed to assess such impacts of AOM and lifestyle intervention with the GLP-1 receptor agonist semaglutide on patients with different obesity classes, i.e. risks (and no diabetes), based on clinical trial data. We estimated the treatment effect on prevalence, medical and indirect costs using the population-attributable fraction approach and various data sources. We modified prevalence data from the Austrian Health Interview Survey 2019 (n = 15,461) using data about proportional weight reductions after the treatment with semaglutide as an adjunct to lifestyle intervention. In a life-cycle model, we compared the costs of obesity classes. Treating 50% of patients with obesity class II and III (excl. diabetes patients, including patients not responding to the treatment) over 68 weeks, reduced the prevalence from 4% to 2.74% (95% CI 2.739–2.743) and from 1.45% to 0.97% (95% CI 0.969–0.997), respectively. This resulted in a reduction of 12.9% (€ − 108.7 million) of expenses related to obesity class II and III per year. Over the life cycle, a reduction in obesity class reduced costs by about 40% per patient. The newer AOM can aid in reducing moderate- and high-risk obesity rates and bring economic and health benefits to society, given that AOM are available and affordable for the respective populations.